Characteristics and related factors of family functioning in Chinese families during early pregnancy - Qin, Xuemei; Zhang, Weiling; Xu, Shuyin; Ma, Mohan; Fan, Xing; Nie, Xueqing; Liu, Jin; Ju, Yumeng; Zhang, Li; Li, Lingjiang; Li, HaoLun; Liu, Bangshan; et al. (Frontiers in Psychology, 2023)
Family functioning has been found to significantly impact each family member’s health mentally, physically, and socially. A number of the research has focused on the impact of impaired family functioning in general, but limited studies explore family functioning in the vulnerable period, early pregnancy. Therefore, we aimed to investigate the characteristics and related factors in Chinese females and partners during early pregnancy. The cross-sectional study enrolled 226 pregnant women and 166 partners. Assessment tools included the McMaster Family Assessment Device (FAD), Edinburgh Postnatal Depression Scale, Patient Health Questionnaire-9, Generalized Anxiety Disorder 7-Item, Social Support Rating Scale, and Quality of Life Enjoyment and Satisfaction Questionnaire, Short Form. Correlation analysis was applied to investigate the related factors. In the present study, FAD-Behavior Control (BC) was the only dysfunctional dimension and had the highest dysfunctional rates than other dimensions. Length of time living with a partner, depressive and anxious symptoms, and quality of life were all associated with the dysfunctional family functioning of BC. The study reinforced the important clues of family functioning during early pregnancy. Also, it provided new entry points for the general population and healthcare providers to minimize the negative impact that impaired family function might bring to a family.